Brief history of herpetology in the Museum of Vertebrate Zoology, University of California, Berkeley, with a list of type specimens of recent amphibians and reptiles - Rodríguez-Robles, Javier A.; Good, David A., 1956-; Wake, David B. (University of California publications in zoology, 2003)
The Museum of Vertebrate Zoology (MVZ), located on the campus of the University of California, Berkeley, is a leading center of herpetological research in the United States. This book offers a brief account of the principal figures associated with the collection and of the most important events in the history of herpetology in the MVZ during its first 93 years, and lists all type specimens of recent amphibians and nonavian reptiles in the collection.